For this case we have the following system of equations:
[tex]-5x-y = 38\\-6x-3y = 60[/tex]
To solve the system we follow the steps below:
We multiply by -3 the first equation:
[tex]15x + 3y = -114[/tex]
We have the following equivalent system:
[tex]15x+3y=-114\\-6x-3y=60[/tex]
We add the equations:
[tex]9x = -54\\x = - \frac {54}{9}\\x = -6[/tex]
We look for the value of the variable "y":
[tex]-5x-y = 38\\-5 (-6) -y = 38\\30-y = 38\\-y = 38-30\\-y = 8\\y = -8[/tex]
The system solution is given by:
[tex](x, y): (- 6, -8)[/tex]
Answer:
[tex](x, y): (- 6, -8)[/tex]